2022
DOI: 10.7759/cureus.31893
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Statins and Breast Cancer in Mouse Models: A Systematic Review

Abstract: Statins, a class of cholesterol-lowering drugs, have consistently demonstrated pleiotropic effects in both preclinical and clinical studies. Outside of inhibiting the production of cholesterol in cells, statins have shown antineoplastic properties most commonly in breast cancer. Clinical and epidemiological studies, however, are less definitive than preclinical studies regarding statins as potential adjuvant oncologic therapy. Our objective is to summarize mouse model studies that investigate the link between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…After the approval of lovastatin, six statins have been introduced into the market. [110] In addition to the cholesterol inhibition activity, statins also exhibit anticancer activity. In breast cancer cells, statins decreased cell proliferation and increased apoptosis.…”
Section: Statinsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the approval of lovastatin, six statins have been introduced into the market. [110] In addition to the cholesterol inhibition activity, statins also exhibit anticancer activity. In breast cancer cells, statins decreased cell proliferation and increased apoptosis.…”
Section: Statinsmentioning
confidence: 99%
“…It was approved by USFDA and indicated for treatment of coronary artery diseases and hypercholesterolemia. After the approval of lovastatin, six statins have been introduced into the market [110] . In addition to the cholesterol inhibition activity, statins also exhibit anticancer activity.…”
Section: Natural Products In Breast Cancer Treatmentmentioning
confidence: 99%
“…The most frequent intracranial tumors in adults are brain metastases (BM), and many studies have investigated the possible impact of statins in preventing and treating BM from breast cancer [ 42 , 111 , 112 ]. Most molecular research studies on the risk of metastatic spread have been conducted on breast cancer with early staging and showed that markers such as p16 kinase inhibitor, which is a tumor suppressor protein, is linked to the development of BM with metastatic lymph nodes from breast cancer patients [ 113 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer (BC) is not a single illness but a collection of diverse subtypes with varying clinical outcomes. It accounts for around 12.5% of all new annual cancer diagnoses [1] . Currently, the treatment of BC includes surgery that is, breast conservation or mastectomy, radiation, chemotherapy, hormone therapy, targeted therapy medications, immunotherapy, and/or supportive care [2] .…”
mentioning
confidence: 99%
“…The antineoplastic benefit of statins as single agents in mouse model studies helps inform their synergistic use that future clinical trials can test. Parameters such as statin dose, timing, and BC subtype are essential steppingstones in defining how this drug could treat BC [12] .…”
mentioning
confidence: 99%